Analysis of the Use of E-Perda in the Formation of Digital-Based Regional Legal Products - Satria, Eko; Zubair, Zubair; Novianti, Wa Ode (Universitas Pancasakti, 2025)
This study analyzes the implementation of the E‑Perda application as a digital instrument for forming local legal products in Baubau City and South Buton Regency. Using a doctrinal legal method and an evidence‑based policy approach, we conducted literature review, document analysis, and benchmarking with Pare‑Pare City and Banggai Laut Regency to assess regulatory readiness, digital literacy of human resources, and digital infrastructure. Results reveal that despite relatively adequate infrastructure, Baubau and South Buton have not adopted E‑Perda due to the absence of binding mandates, limited digital capacity, and institutional resistance, indicating a clear gap between policy and practice. This research highlights that E‑Perda can bridge those gaps by enhancing legislative efficiency, transparency, and accessibility in remote areas, but only if supported by strong political commitment, regulatory reform, and capacity‑building initiatives. By providing comparative evidence on these implementation challenges, the study offers practical insights for policymakers seeking to advance digital governance in Indonesia.